2021
DOI: 10.1136/bmj.n1022
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral interventions to improve population health outreach for hepatitis C screening: randomized clinical trial

Abstract: Objective To evaluate whether opt out framing, messaging incorporating behavioral science concepts, or electronic communication increases the uptake of hepatitis C virus (HCV) screening in patients born between 1945 and 1965. Design Pragmatic randomized controlled trial. Setting 43 primary care practices from one academic health system (Philadelphia, PA, USA) between April 2019 and May 2020. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“… 4 , 5 , 6 However, these same biases can often be overcome or even harnessed with different message frames that increase uptake of screening and vaccination. 7 , 8 , 9 The concept of endowment suggests that people place higher value on items in their possession. If the vaccine is described as already reserved for the patient, that approach could take advantage of this sense of ownership, as patients may feel remorse giving up the allocated vaccine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 4 , 5 , 6 However, these same biases can often be overcome or even harnessed with different message frames that increase uptake of screening and vaccination. 7 , 8 , 9 The concept of endowment suggests that people place higher value on items in their possession. If the vaccine is described as already reserved for the patient, that approach could take advantage of this sense of ownership, as patients may feel remorse giving up the allocated vaccine.…”
Section: Introductionmentioning
confidence: 99%
“…The second approach was to deploy insights from the field of behavioral science, as humans have systematic biases or heuristics that impede participation in health prevention activities . However, these same biases can often be overcome or even harnessed with different message frames that increase uptake of screening and vaccination . The concept of endowment suggests that people place higher value on items in their possession.…”
Section: Introductionmentioning
confidence: 99%
“…Yartel et al conducted a cluster randomized trial at an academic medical center and found that a conventional interruptive best-practice alert to the medical assistant and clinician in a primary care setting resulted in an increase in screening completion from 3.6% in the control group to 30.9% in the intervention group. Another trial in the primary care setting at our own health system showed that bulk ordering with opt-out framing increased HCV screening from 19.2% to 43.1%. Interestingly, in the outpatient setting, only 0.4% of screening tests completed were positive for viral load, whereas 1.6% were positive in the previous study, suggesting that inpatients may have a higher risk of HCV.…”
Section: Discussionmentioning
confidence: 99%
“…He reported that rates doubled, from 19% to 43%. 6 But perhaps the most actionable step, Dr. Mehta said, is to require families and adolescents to "opt out" rather than "opt in" for the vaccine. In other words, make vaccination the default option, which ensures it is easier to get the vaccine than to refuse it.…”
Section: Leveraging Insights From Behavioral Economicsmentioning
confidence: 99%